(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Siamese fighting fish or bettas are highly favoured for their aesthetical value and kept as ornamental fish. They are widely bred to satisfy the market demands. However, large-scale production of bettas is hampered by the relatively high rate of mortality compared to the number of eggs laid. The nutrition intake literally influences the reproductive performance and eggs quality. Therefore, it is plausible to improve the survivability of betta fry through dietary manipulation. Bettas can be fed with a variety of feeds. Bloodworms and commercially available pellets are commonly used. Fruit fly maggots emerged as potential anti-infective agents and have been used as alternative fish feed. Therefore, this study aims to harness the beneficial properties of maggots to enhance reproductive performance and increase the survivability of the bettas. The effects on fecundity, eggs hatchability and fry survivability of maggot feed were compared with the other common feed, namely bloodworms and commercial pellet. The results showed that maggots can serve as an alternative feed for bettas whereby it gave an average hatchability rate of 65% and survivability rate of 69%. Although the mean hatchability and survivability rate did not differ significantly from the other two feeds, this study suggests the attainable yet economic feeding material, has the potential to inaugurate further studies to enhance the production of bettas on large scale.